2012
DOI: 10.1021/cb3001099
|View full text |Cite
|
Sign up to set email alerts
|

A Competitive Nucleotide Binding Inhibitor: In Vitro Characterization of Rab7 GTPase Inhibition

Abstract: Mapping the functionality of GTPases through small molecule inhibitors represents an underexplored area in large part due to the lack of suitable compounds. Here we report on the small chemical molecule 2-(benzoylcarbamothioylamino)-5,5-dimethyl-4,7-dihydrothieno[2,3-c]pyran-3-carboxylic acid (PubChem CID 1067700) as an inhibitor of nucleotide binding by Ras-related GTPases. The mechanism of action of this pan-GTPase inhibitor was characterized in the context of the Rab7 GTPase as there are no known inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 54 publications
3
81
1
Order By: Relevance
“…Briefly, hepatocytes suspended in Williams’ E media were seeded onto collagen‐coated six‐well plates with or without coverslips. After 2 hours at 37°C, cells were washed with phosphate‐buffered saline (PBS) and incubated for 4 hours in either Williams’ E media with 5% fetal bovine serum or in the nutrient‐free buffer Krebs‐Ringer‐4‐(2‐hydroxyethyl)‐1‐piperazine ethanesulfonic acid (HEPES) (KRH) either with or without 80 µM CID1067700 (Rab7‐specific inhibitor) 20, 27. Following the incubation period, cells were collected and the pellets reconstituted in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, hepatocytes suspended in Williams’ E media were seeded onto collagen‐coated six‐well plates with or without coverslips. After 2 hours at 37°C, cells were washed with phosphate‐buffered saline (PBS) and incubated for 4 hours in either Williams’ E media with 5% fetal bovine serum or in the nutrient‐free buffer Krebs‐Ringer‐4‐(2‐hydroxyethyl)‐1‐piperazine ethanesulfonic acid (HEPES) (KRH) either with or without 80 µM CID1067700 (Rab7‐specific inhibitor) 20, 27. Following the incubation period, cells were collected and the pellets reconstituted in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…However,s everal high-throughput screens (HTSs) identified compounds interfering with GTPase nucleotide binding in vitro. [49][50][51] By using ab ead-based flow cytometry assay [52] to test 300 000 compounds,CID1067700 (1)was identified as adirect competitor for nucleotide binding (Figure 3a). [49] This compound impairs nucleotide binding by several small GTPases with low nanomolar inhibitory constants (K i = 12.9-19.7 nm) in vitro.I na ni dentical setup,C ID29950007 (ML141, 2)w as identified as aC dc42-selective noncompetitive allosteric inhibitor (Figure 3a).…”
Section: Interference With Nucleotide Bindingmentioning
confidence: 99%
“…[49][50][51] By using ab ead-based flow cytometry assay [52] to test 300 000 compounds,CID1067700 (1)was identified as adirect competitor for nucleotide binding (Figure 3a). [49] This compound impairs nucleotide binding by several small GTPases with low nanomolar inhibitory constants (K i = 12.9-19.7 nm) in vitro.I na ni dentical setup,C ID29950007 (ML141, 2)w as identified as aC dc42-selective noncompetitive allosteric inhibitor (Figure 3a). [50] In this case,t he binding of 2 locks Cdc42 in an inactive conformation, thereby inducing nucleotide release and inhibition of Cdc42-mediated cellular functions such as filopodia formation or cell migration (Figure 3b).…”
Section: Interference With Nucleotide Bindingmentioning
confidence: 99%
“…Acyl thiourea compounds, cambinol and tenovin-1 are small molecule inhibitors of the NAD + -dependent family of protein deacetylases that is one of the targets in the treatment of cancer and neurodegenerative diseases (13,14). In the other research, CID 1067700 carrying acyl thiourea structure has been reported as an inhibitor of nucleotide binding by Ras-related GTPases (15). In addition, N-substituted phenylthioureas have been found that have antitumoral effects against skin cancer (16,17).…”
Section: Introductionmentioning
confidence: 99%